Language personality of a preschool child: features of development in the process of listening - Nataliia V. Kharchenko (Психолінгвістика, 2017)
The article focuses on opening of the problem of study the phenomenon of language personality in modern psychological science as a social new formation, subject of interpersonal relations, the man, which owns a set of language skills, properties and capabilities. The research aim is to present the authorial formulation of the concept «development of language personality of a preschool child in the process of listening»; determination of terms and psychodidactic receptions of the development of language personality of a preschool child in the process of listening. In order to achieve the aim were used such methods: analysis of psycholinguistic and psychological literature, integration of derived from the analysis data, formulation of concepts «language personality», «development of language personality of a preschool child in the process of listening», systematization of the generalized information from theoretical research, formulation of conclusions. Research results enabled us to formulate authorial determination of the concept “development of language personality of a preschool child in the process of listening”, which we understand as the complecated process of child’s special relationships acquisition with the subjective and social world in a form of communication, operations and capabilities, new possibilities of perception and understanding of the language values, their transformation into personal senses, his becoming as a subject of communicative co-operation, a person, whomastered because of vocal (аuditive) activity on realization of this communicative co-operation the new special capabilities, competenses and qualities, which form a child as personality.